ANALISIS WACANA DALAM LIRIK LAGU MANDARIN KARYA JOKER XUE薛之谦 - Cindy Lestari; Septerianie Sutandi (Universitas Warmadewa, 2023)
Discourse is the highest language unit above the clause and has sentences which are interrelated and related both semantically and contextually. The correlation in discourse can be divided into two types, the relevance of form or cohesion and the relevance of meaning or coherence. Through this research, the author will conduct a discourse analysis on the lyrics of Mandarin songs by Joker Xue (薛之谦), the objects of this research are based of Joker Xue’s(薛之谦) love-relationship songs which has a similar theme. Some songs which were taken as objects for this research are《认真的雪》 、《你还要我怎样》 、《深深的爱过你》 今生版 ， and 《演员》. Through this research, the author will analyze the correlation between cohesion and coherence in the lyrics of the songs by Joker Xue (薛之谦) which affects the writing style. The focus of this research is grammatical cohesion, lexical cohesion, and coherence.